A switch in infected erythrocyte deformability at the maturation and blood circulation of Plasmodium falciparum transmission stages - Bischoff, Emmanuel (2013)
Achievement of malaria elimination requires development of novel strategies interfering with parasite transmission, including targeting the parasite sexual stages (gametocytes). The formation of Plasmodium falciparum gametocytes in the human host takes several days during which immature gametocyte-infected erythrocytes (GIEs) sequester in host tissues. Only mature stage GIEs circulate in the peripheral blood, available to uptake by the Anopheles vector. Mechanisms underlying GIE sequestration and release in circulation are virtually unknown. We show here that mature GIEs are more deformable than immature stages using ektacytometry and microsphiltration methods, and that a switch in cellular deformability in the transition from immature to mature gametocytes is accompanied by the deassociation of parasite-derived STEVOR proteins from the infected erythrocyte membrane. We hypothesize that mechanical retention contributes to sequestration of immature GIEs and that regained deformability of mature gametocytes is associated with their release in the bloodstream and ability to circulate. These processes are proposed to play a key role in P falciparum gametocyte development in the host and to represent novel and unconventional targets for interfering with parasite transmission.